Ob izidu zbornika "Psihologija in postmodernizem" - Rutar, Dušan (Psihološka obzorja (Ljubljana), 1993)
We shouldn't think about psychological concepts and practices as they are a neutral epistemological process. The constitution and functioning of psychology as deeply involved in the social. It depends on coexisting practices, institutions and discourses that make them possible. The authors ofthe edition Psychology and Postmodernism don't hide this "involvement" of the psychology, but intend to reconceptualize it incalculating it.
Keywords: Psichology and postmodernism; psihologija; psychology; postmodernizem; ocene in poročila